Iron Therapies For Iron Deficiency In Chronic Kidney Disease: A Literature Review - Zhela Fatin Fatiha; Nining Lestari; Aulia Nissa Rizky Hariyono; Tia Mella Citra; Ayu Mayangsari; Tri Agustina (Publikasi Indonesia, 2022)
Chronic kidney disease is a condition when kidney function fails gradually due to kidney damage. One of the causes of anemia in CKD is iron deficiency. Conventional oral iron treatment is not effective to treat iron deficiency anemia due to poor absorption and various side effects. Newer oral iron therapies with better tolerability and offer the potential to normalize iron without the need for intravenous iron. To review the currently available status oral iron therapies and summarizes the latest clinical trial evidence for their use. We researched Google Scholar and PubMed using keyword